Analisis Berbagai Model Bisnis dalam Produksi Film - Ahmad Budi Sulistioyuwono, S.E, M.M, Ahmad Budi Sulistioyuwono, S.E, M.M (Akademi Komunikasi SAE Indonesia, 2024)
With the entry of new business models such as crowdfunding in the digital age, the film industry has undergone a major transformation. Independent films can get funding directly from their potential audiences because Hollywood's traditional business model has spread to variouscountries around the world, and with the advent of new equipment and distribution platforms, film production has become cheaper. Independent filmmakers have the opportunity to interact directly with their audience through crowdfunding, which allows for filmmaking with diverse viewpoints and narratives. However, there are issues such as attracting and retaining the interest of backers as well as the possible risk of return on investment for backers. With data analysis methods and case studies This research investigates the evolution of film business models, the influence of crowdfunding on diversity of content and viewpoints, interactions between filmmakers and audiences, and changes in interactions between filmmakers and audiences.